Histopathologic features of male domestic cat (Felis domestica) testes induced by bisphenol-A orally - Makmur, Fachira Ulfa; Purba, Fika Yuliza; Sari, Dwi Kesuma (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Infertility in cat becomes a serious problem in pet community since many compounds of infertility-caused can be found widely in the environment. One of the compounds causing infertility in mammals is Bisphenol-A (BPA), which is known as an estrogenic compound. The purpose of this research is to observe the changes in testicular histology of male domestic cat (Felis domestica) induced by BPA orally. Sample used in this study were 24 male domestic cats divided into 4 groups, namely the group 1 as control, group 2, 3 and 4 were treated with BPA about 5, 10 and 100 mg/kg bodyweight, respectively for 5 days. The results showed that the estrogenic effect of BPA affects the reproductive system of the cat. The effects of BPA in cat included decrease in the amounts of spermatozoa, vacuolization of seminiferous tubules cells, degeneration of Leydig cells, degeneration of tubular epithelial cells,  irregular forms of the germ, interstitial tissue hemorrhage, debris cell filled the lumen of seminiferous tubules. These results suggested that BPA can be harmful to the reproductive system of the cat